PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN SUPERVISI KEPALA SE- KOLAH TERHADAP KINERJA GURU - wahyudi, adi (Economic Education Analysis Journal, 2012)
The purpose of  this research is to find out whether there was influences of  working discipline, working motivation, school principal supervision toward working per-formance teachers. The population in this research was 37 teacher’s, determination of  the sample using the formula developed by Isaac & Michael, amounting to 34 teacher’s. Samples were taken using simple random sampling technique. The data collection methods used a closed questionnaire. The analysis technique use were de-scriptive analysis and inferential analysis. The research results are simultaneous the influence of  working discipline, working motivation, and school principal supervi-sion toward working performance teachers is 65.4%. There is a partial influence of  working discipline is 17.56%, work motivation is 27.77%, and school principal supervision of  15:21% toward performance of  teachers. With the existence of  work-ing discipline, working motivation, and school principal supervision can improve teacher performance.